Peranan psikologi pendidikan untuk mencegah bullying pada siswa SMA - Khasanah, Faidatul (Maliki Interdisciplinary Journal, 2024)
The phenomenon of bullying has become one of the pressing issues in the education system in various countries, including Indonesia.The United Nations International Children's Emergency Fund (UNICEF) notes that Indonesia has a high percentage of violence against children, especially among high school students. Educational psychology, as a discipline that studies how individuals learn and develop in the context of education, has an important role in addressing the problem of bullying. This article aims to examine in depth the role of educational psychology in preventing bullying in high school students. Based on the literature study, bullying can occur due to some factors including (1) individual; a person's personality, emotional problems, and aggressive behavior, (2) family; parenting, family dynamics, family economy, and parental influence, (3) school environment; school culture, relationships between students, teacher behavior as a role model for students, and school policies, and (4) environment and social media related to where a person lives and media consumption. Bullying prevention strategies can be carried out through preventive (character education, increasing empathy, and strengthening positive values) and intervention (implementing individual counseling and peer support programs) approaches